Recruitment and Retention Challenges Weavers of Bali Endek Weaving Industry - Ganaki Pusparani, Luh Made Diah; Gede Sri Darma (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2025)
This study aims to analyze the challenges of recruitment and retention of weavers in the Balinese endek weaving industry using the Analytic Hierarchy Process (AHP) method. Endek as one of Bali's cultural heritages has high aesthetic, historical, and economic value, but its sustainability faces serious challenges due to the regeneration crisis and the low attractiveness of the weaving profession. This study involved six main criteria, namely: work environment, stability, salary, compensation, career development, and involvement. The AHP results show that the work environment has the highest weight (0.188), followed by work stability (0.148), and compensation (0.225) which, although high in weight, are not consistent in perception. These findings indicate that the main challenges in retention lie in the structural aspects and work welfare, while challenges in recruitment are closely related to the low interest of the younger generation and the lack of career development. Based on these findings, a strategy for strengthening recruitment is formulated through cultural campaigns, regenerative training, and educational collaboration, as well as a strategy for increasing retention through improving the work environment, guaranteeing stability, and productivity-based incentives. This study suggests strengthening the endek weaving industry ecosystem sustainably through a pentahelix approach involving the government, academics, communities, business actors, and the media.